Autophagy machinery plays an essential role in traumatic brain injury-induced apoptosis and its related behavioral abnormalities in mice: focus on Boswellia Sacra gum resin - Interdonato, Livia; Marino, Ylenia; Impellizzeri, Daniela; D’Amico, Ramona; Siracusa, Rosalba; Fusco, Roberta; Cammilleri, Gaetano; Pantano, Licia; Modafferi, Sergio; Abdelhameed, Ali S.; Fritsch, Tilman; Rashan, Luay J.; et al. (Frontiers in Physiology, 2024)
Traumatic brain injury (TBI) is described as a structural damage or physiological disturbance of brain function that occurs after trauma and causes disability or death in people of all ages. New treatment targets for TBI are being explored because current medicines are frequently ineffectual and poorly tolerated. There is increasing evidence that following TBI, there are widespread changes in autophagyrelated proteins in both experimental and clinical settings. The current study investigated if Boswellia Sacra Gum Resin (BSR) treatment (500 mg/kg) could modulate post-TBI neuronal autophagy and protein expression, as well as whether BSR could markedly improve functional recovery in a mouse model of TBI. Taken together our results shows for the first time that BSR limits histological alteration, lipid peroxidation, antioxidant, cytokines release and autophagic flux alteration induced by TBI.